Mothers’ Acceptance and Willingness to Pay an Out-of-Pocket Payment for Maternal and Child Nutritional Services in Northwest Ethiopia - Amare G; Yitayal M; Minyihun A; Debie A (Dove Medical Press, 2021)
Getasew Amare, Mezgebu Yitayal, Amare Minyihun, Ayal Debie Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Getasew AmareDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, P.O. Box 196, Gondar, EthiopiaEmail getasewa23@gmail.comBackground: Around $3.5 trillion globally and up to $2.78 billion in Ethiopia, losses are reported annually due to malnutrition. Even if in Ethiopia nutrition services are delivered free of charge, specific public health programs may start to charge users of services that include maternal and child health services. Therefore, this study was aimed to assess mothers' willingness to pay an out-of-pocket payment for maternal and child nutritional services and associated factors in Northwest Ethiopia.Methods: A community-based cross-sectional study design was conducted at Yilmana Densa district from March to May 2017. The sample size was 569, and a systematic random sampling technique was used. Bi-variate, multivariable logistic regression, and Tobit econometric analysis models were done. Adjusted odds ratio (AOR) and B-coefficient with 95% confidence interval (CI) and p-value were used.Results: A total of 545 (response rate of 95.8%) study participants were included in the study. The finding indicates that 88.8% of households were willing to pay for maternal and child nutrition services. The average amount of money to pay per visit was 19.6 ETB (CI = 18.8, 20.4) (0.84 USD). Mothers with good knowledge, good perceived family health status, medium and high perceived quality of services, and satisfaction with maternal and child nutritional services were significant variables to accept an out-of-pocket payment. In addition, the Tobit econometric model analysis reveals that knowledge, mothers' age, pregnancy status, mothers' educational status, wealth status, and self-reported satisfaction were identified as significant factors.Conclusion: The majority of mothers were willing to accept out-of-pocket payments for maternal and child nutritional services with an average of 19.6 ETB. Therefore, strengthening awareness and improving the quality of nutritional services and maternal satisfaction may increase mothers' willingness to pay an out-of-pocket payment.Keywords: willingness to pay, Tobit model, maternal and child nutritional services, northwest Ethiopia